Questions Regarding the Implementation of EU Mutagenesis Ruling in France - Bartsch, Detlef; Ehlers, Ulrich; Hartung, Frank; Kahrmann, Jens; Leggewie, Georg; Sprink, Thorben; Wilhelm, Ralf (Frontiers in Plant Science, 2020)
The European Commission has asked EU Member States for comments on a French law notification demanding plant varieties produced with the help of in vitro mutagenesis have to be eliminated from the national catalogue of approved varieties because of missing legal authorization deemed required by genetic engineering law. Primary target are herbicide-tolerant Clearfield oilseed rape varieties. The legal and scientific reasoning is questionable and the implications on traceability and law enforcement nearly impossible. The notification by France should therefore be rejected by the European Commission.